Designing a Prototype Information System for a Building Material Store using the Zachman Framework - Adzikra, Kaysha Soffa Marwa Nabila; Saepudin, Sudin; Ekasatria, Hendri; Mupaat, Mupaat (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The growing need for digitalization of business processes in the retail sector requires information systems capable of supporting operational efficiency and accurate decision-making. This study aims to design an inventory management information system for CV. Berjuang Sakti using an Enterprise Architecture approach based on the Zachman Framework. The previously applied manual system had led to several issues, including inaccurate record-keeping, data inconsistencies, and delayed reporting. The Zachman Framework was applied to structure the system design across six main perspectives: Planner, Owner, Designer, Builder, Implementer, and User. The design results include stakeholder-based requirements analysis, system modeling (ERD, Use Case Diagram, and Activity Diagram), and a user interface prototype featuring real-time stock tracking, transaction management, and reporting. Usability testing using the System Usability Scale (SUS) with 15 respondents produced a score of 72.3, categorized as “Good,” indicating that the system is feasible and effective in supporting the daily operations of CV. Berjuang Sakti. These findings provide practical implications for improving efficiency and accuracy in inventory management through the adoption of a structured and measurable system architecture.